Eat Well to Fight Obesity… and Save Water: The Water Footprint of Different Diets and Caloric Intake and Its Relationship With Adiposity - Lares-Michel, Mariana; Housni, Fatima Ezzahra; Aguilera Cervantes, Virginia Gabriela; Carrillo, Presentación; Michel Nava, Rosa María; Llanes Cañedo, Claudia (Frontiers in Nutrition, 2021)
Water scarcity and excess adiposity are two of the main problems worldwide and in Mexico, which is the most obese country in the world and suffers from water scarcity. Food production represents 90% of a person’s water footprint (WF), and healthy diets can lead to less WF than do unhealthy diets related to obesity. We calculated the WF of the diet and caloric intake of adults in Mexico and analyzed its relationship with adiposity. Also, the risk of water expenditure due to adiposity and adherence to dietary recommendations regarding WF of international healthy diets were examined. A Food Consumption Frequency Questionnaire (FCFQ) was applied to 395 adults. Body Mass Index (BMI), associated with adiposity indicators, was used as a reference for grouping sample into adiposity levels. The WF was calculated according to the WF Assessment Method, considering correction factors and accounting for water involved in cooking and food washing. Our results showed that the Mexican diet spends 6,056 liters per person per day (L p-1d-1) and is 55% higher than international healthy diets WF. Consumption of beef, milk, fruits, chicken, and fatty cereals represented 56% of total WF. Strong relations appeared between hypercaloric diets and high WF. Diets of people with excess adiposity generated statistically higher WF with extra expenses of 729 L p-1d-1 compared to the normal adiposity population. Following nutritional recommendations offers a protective factor for water care whereas not adhering to these represents a risk up to 93 times greater of water expenditure regarding international healthy diets. Therefore, both for the general population and to regulate obesity, adequate diets can help mitigate the problem of water scarcity.